Byzantine spirit of the Undead and its legacy in the Sick Man of Europe - Tešan, Jesenko; Davison, Joan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper examines the source and consequences of permanent liminality in the political-legal administration of the Byzantine Empire. The paper argues ambiguous and incomplete identities of individuals, groups, and society associated with certain authoritarian political arrangements and consequent arrested liminal period(s) contributed to the decline of the Empire. Further, and significantly, the unresolved situation of disaggregated identity, or spirited away demos, persisted in the Ottoman Era and continues to infect contemporary socio-political affairs in regions in the Balkans and other countries of the former Soviet Union which now seek to balance the interests of a nation-state with the diversity of Europe.
Keywords: Byzantine; Ottoman; liminality; demos; millets